2010
DOI: 10.1016/j.ehb.2010.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Health trends in Sub-Saharan Africa: Conflicting evidence from infant mortality rates and adult heights

Abstract: We investigate trends in cohort infant mortality rates and adult heights in 39 developing countries since 1960. In most regions of the world improved nutrition, and reduced childhood exposure to disease, have lead to improvements in both infant mortality and adult stature. In Sub-Saharan Africa, however, despite declining infant mortality rates, adult heights have not increased. We argue that in Sub-Saharan Africa the decline in infant mortality may have been due to interventions that prevent infant deaths rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 65 publications
3
31
0
Order By: Relevance
“…A study of trends in height, health, and infant mortality in sub-Saharan Africa showed that, although infant mortality had improved since 1961, average adult heights had not increased. 64 …”
Section: Patterns Of Modern Adult Height Secular Increasesmentioning
confidence: 99%
“…A study of trends in height, health, and infant mortality in sub-Saharan Africa showed that, although infant mortality had improved since 1961, average adult heights had not increased. 64 …”
Section: Patterns Of Modern Adult Height Secular Increasesmentioning
confidence: 99%
“…While reductions in these morbidities contribute to the impact of vitamin A on all-cause mortality, that impact is likely also bolstered by the ability of vitamin A to increase T-cell counts, particularly of the CD4 population, in children infected with HIV. Akachi and Canning (2010) argue that improving nutrition and reducing morbidity should be a key focus for development interventions, as child morbidity is a strong predictor of later-life outcomes. Indeed, individuals experiencing high levels of childhood morbidity have been shown to have reduced cognition, impaired adult stature, and be at increased risk of later-life morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…2 In Sub-Saharan Africa in particular, achievements in reducing child mortality may have outpaced reductions in childhood morbidity. This hypothesis is based on the fact that, despite advances in reducing child mortality in Africa, today's adult Africans are shorter than their predecessors, which may be an indicator of increased childhood morbidity (Akachi & Canning, 2010). Reducing childhood morbidity may prove an effective and sustainable option for improving the productivity and longevity of the next generation of Africans.…”
Section: Introductionmentioning
confidence: 99%
“…The current study compared the cross-sectional data and found that countries with higher national income have lower mortality rate and developed economy can help to reduce mortality largely due to improvements in immunization programs, considering the maternal status, education level in society, medical technology and the availability of maternal and infant health care services. In other words, improvement in declining infant mortality rate worldwide in the 20 th century was associated with improved education, income and public health (7,8).…”
Section: Introductionmentioning
confidence: 99%